Können pathologische Hypertrophie des linken Venrtikels und arterielle Hypertension von durch Sport hervorgerufener physiologischer Hypertrophie unterschieden werden? - Schannwell, C. M.; Marx, R.; Plehn, G.; Perings, C.; Leschke, M.; Strauer, B. E. (Deutsche Medizinische Wochenschrift, 2001)
Patients with hypertensive heart disease and left ventricular hypertrophy demonstrate impaired left ventricular diastolic filling. Aim of this study was to find out if physiological left ventricular hypertrophy induced by endurance training causes abnormal left ventricular systolic and diastolic filling. METHODS: We examined 42 athletes with left ventricular hypertrophy due to endurance training (aged 25 +/- 7 years), 31 patients with left ventricular hypertrophy due to hypertensive heart disease (aged 28 +/- 6 years) and 20 untrained, healthy subjects (controls, aged 26 +/- 8 years) by conventional echocardiography and calculated left ventricular muscle mass and fractional shortening. In addition the following Doppler-echocardiographic parameters were measured: maximal early and late velocity of diastolic filling, ratio of maximal early and late velocity of diastolic filling, acceleration and deceleration time and isovolumetric relaxation time. RESULTS: All three study groups showed normal fractional shortening. Conventional echocardiography revealed a higher left ventricular muscle mass in the two study groups as compared to the controls (controls: 119 +/- 12 g, athletes: 225 +/- 18 g*; hypertensive patients: 216 +/- 16 g*; * p < 0.01 versus controls). In the athletes with physiological left ventricular hypertrophy a normal left ventricular diastolic filling pattern was documented (VE: 0.64 +/- 0.1 m/s; VA: 0.51 +/- 0.2 m/s). In hypertensive heart disease a diastolic dysfunction in terms of a delayed relaxation pattern with a decrease of maximal early velocity of diastolic filling (VE: 0.45 +/- 0.09 m/s) and a compensatory increase of the maximal late velocity of diastolic filling (VA: 0.54 +/- 0.1 m/s) was demonstrated. CONCLUSION: In pathological left ventricular hypertrophy due to hypertensive heart disease a pathological diastolic filling pattern was documented. In athletes with physiological left ventricular hypertrophy a normal left ventricular diastolic filling pattern was revealed. Thus Doppler-echocardiographic parameters of left ventricular diastolic function can be of diagnostic importance for discriminating between pathological and physiological left ventricular hypertrophy.